Dam Construction in Lancang‐Mekong River Basin Could Mitigate Future Flood Risk From Warming‐Induced Intensified Rainfall. Issue 20 (25th October 2017) - Wang, Wei; Lu, Hui; Ruby Leung, L.; Li, Hong‐Yi; Zhao, Jianshi; Tian, Fuqiang; Yang, Kun; Sothea, Khem
Abstract: Water resources management, in particular flood control, in the Lancang‐Mekong River Basin (LMRB) faces two key challenges in the 21st century: climate change and dam construction. A large‐scale distributed Geomorphology‐Based Hydrological Model coupled with a simple reservoir regulation model (GBHM‐LMK‐SOP) is used to investigate the relative effects of climate change and dam construction on the flood characteristics in the LMRB. Results suggest an increase in both flood magnitude and frequency under climate change, which is more severe in the upstream basin and increases over time. However, stream regulation by dam reduces flood risk consistently throughout this century, with more obvious effects in the upstream basin where larger reservoirs will be located. The flood mitigation effect of dam regulation dominates over the flood intensification effect of climate change before 2060, but the latter emerges more prominently after 2060 and dominates the flood risk especially in the lower basin. Key Points: The model coupled with reservoir regulation realistically simulated the effects of dams on floods in the Lancang‐Mekong River Basin Climate change increases flood magnitude and frequency, but reservoir regulation reduces flood risk particularly in the upper basin Combining climate change and reservoir regulation, flood risk is reduced in the upper basin but still increases in the lower basin Plain Language Summary: In this study, we present a model‐based projection of flood risk in Lancang‐Mekong River. It is found that the basin will experience more frequent and bigger flood events in the future in response to climate change. Through reservoir regulation, flood risk can be mitigated particularly in the upper basin where large reservoirs are located. Combining climate change and reservoir regulation, flood risk is reduced in the upper basin but the increased flood magnitude and frequency from climate change still dominant in the lower basin.